Coarse-grained molecular simulation of the effects of carbon nanotube dispersion on the mechanics of semicrystalline polymer nanocomposites - Wu,C; Wu,R; Tam,L-H (Nanotechnology, 2021)
With the incorporation of carbon nanotubes (CNTs), CNT/polypropylene (PP) nanocomposites are found to possess enhanced mechanical properties, but the reinforcing effect is reduced at large added CNT weight percentages due to CNT aggregation. Optimizing the properties of a nanocomposite requires a fundamental understanding of the effects of CNT dispersion on the nanocomposite. In this work, coarse-grained molecular models of CNT/PP nanocomposites are constructed, which consist of randomly dispersed or aggregated CNT bundles. Our simulation results reveal that with randomly dispersed CNT bundles, the nanocomposite shows properties that continuously improve with increasing CNT contents due to the effective CNT/PP interface and the reinforcing effect of CNTs. By comparison, the nanocomposite with aggregated CNT clusters exhibits a decline in yield strength at CNT contents over 3 wt%, which results from a reduced CNT load-carrying capacity due to the formation of structural voids in the interfacial region. This study achieves an in situ observation of the structural void evolution of loaded nanocomposites, provides valuable insights into the effects of CNT dispersion on the mechanics of CNT/PP nanocomposites, and paves the way for optimizing the design of nanocomposites with superior mechanical properties by designing the CNT dispersion in the structure.